2022
DOI: 10.1101/2022.04.28.489871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyphyly of theNiphargus stygiusspecies group (Crustacea, Amphipoda, Niphargidae) in the Southern Limestone Alps

Abstract: The Niphargus stygius species complex is a groundwater group of large-sized, sexually dimorphic species inhabiting mainly caves and, less frequently, wells and springs. According to the taxonomists of the last century, this species complex was supposed to be present in the whole Southern Limestone Alps of Italy as well as in peninsular Italy and Slovenia. Considering the large presumed distribution area, we tested the contrasting hypotheses of monophyly versus paraphyly of this subterranean species complex, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This might be a residue of sampling effort. Nevertheless, previous studies found multiple stygobiont species, including groundwater amphipods of the genus Niphargus , to be distributed at LGM glacier margins along the Alps (Foulquier et al 2008, Mammola et al 2019b, Weber et al 2021, Stoch et al 2022). Such findings support the hypothesis that some species distribution ranges might have been limited to unglaciated areas during Pleistocene glacier expansions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be a residue of sampling effort. Nevertheless, previous studies found multiple stygobiont species, including groundwater amphipods of the genus Niphargus , to be distributed at LGM glacier margins along the Alps (Foulquier et al 2008, Mammola et al 2019b, Weber et al 2021, Stoch et al 2022). Such findings support the hypothesis that some species distribution ranges might have been limited to unglaciated areas during Pleistocene glacier expansions.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated community composition changes of subterranean amphipod species along a Late Pleistocene glaciation gradient and revealed how contemporary biodiversity patterns are shaped by the presence/absence of ice during the LGM. In contrast to above‐ground species (Parisod 2008, Jardim de Queiroz et al 2022), contemporary subterranean amphipod communities are not only shaped by refugial persistence in unglaciated regions and subsequent recolonizations (Foulquier et al 2008, Stoch et al 2022), but also have strong patterns of persistence in groundwater habitats covered by ice over extensive periods. These regions are characterized by distinct yet species‐poor communities that have a lower spatial turnover than communities in unglaciated areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it could indicate ecological gradients, possibly enforced by Pleistocene glaciations, prompted speciation through so called “speciation pumps”(Hu et al, 2021), and species rich regions emerge at the junction of species from different elevations. Intensified speciation at mountain slopes is well-known for freshwater amphipods in general (Copilaş-Ciocianu & Petrusek, 2015; Liu et al, 2023; Mamos, Wattier, Majda, Sket, & Grabowski, 2014) and Niphargus in particular (Delić et al, 2021; Lefébure et al, 2007; Stoch, Salussolia, & Flot, 2022). Interestingly, the map showing the biodiversity pattern of MOTUs is similar to the map showing biodiversity pattern of clades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The total length of the concatenated dataset was 2,070 bp. Considering the presence of heterozygous bases in the third codon position of H3 and the saturation (for transversions as well as for transitions) of the third codon positions of coi demonstrated for Niphargidae by Stoch et al (2023), only the first and second H3 and coi codon positions were retained for phylogenetic analyses. The best partitioning scheme and optimal substitution models for the codon positions were searched using PartitionFinder 2.1.1 (Lanfear et al, 2017) and are listed in supplementary table S2.…”
Section: Phylogenetic Analysismentioning
confidence: 99%